PERKEMBANGAN PERBANKAN DAN PROBLEM INTERMEDIASI - Abdul Manap Pulungan; Ahmad Erani Yustika (Jurnal Keuangan dan Perbankan, 2012)
After economy crisis in 1997/1998, gradually banking intermediation had held its function again although untilnow it was still far from what it was hoped. Some banks had already fulfilled the regulation of Indonesia Bank togive credit more than 78% (LDR), but there were still many banks that had not fulfilled the regulation. Thefactors of high interest rate, banking efficiency, and economy infrastructure availability were considered as thefactors that impeded the banking intermediation function. Not all those problems belonged to Indonesia Bank.However, some of them were the homework for government (like economy infrastructure supplying). Thus,cooperation between Indonesia Bank and government was something that had to be done to finish the problem.Besides, there were other problems that needed to be paid attention in bank performance that was gradually better.They were: (1) banking credit which was farther from real sector (agriculture and industry); (2) credit which wasnot evenly distributed in all areas (3) savings dominated by short term fund; (4) banking structure which tendedoligopoly; and (5) most savings or fixed deposits which were dominated by few account owners.